Necessidades hídricas das culturas milho e feijão-caupi influenciadas pelas mudanças climáticas no semiárido nordestino - Cavalcante Junior, Edmilson Gomes (Universidade Federal Rural do Semi-Árido, 2015)
The overall objective of this study was to assess the impacts that climate change may lead to the development and evapotranspiration of maize and cowpea in the Brazilian semiarid region. The study was conducted in the municipalities of Apodi, Ipanguaçu and Mossoro, the state of Rio Grande do Norte. The determination of crop evapotranspiration, in its different phases, was held by lysimeters of weighing. To check the influence of climate change on culture water consumption were simulated changes in the temperature and relative humidity of the air, through the PRECIS climate model. We evaluated two scenarios of emissions based on the report Intergovernmental Panel on Climate Change: a pessimist called A2 and optimistic B2. The corn crop coefficient suffered greater influence of climate change, because culture has a higher size compared to the reference culture thereby its aerodynamic properties were more influenced by the reduction in relative humidity simulated by the model. Temperatures will be well above the limit tolerated by crops, which could have a negative impact on their development and productivity. With rising temperatures, both cultures have their reduced cycle. The reduction in the cycle also cause a decrease in the total evaporation of the cultures. With the additions expected in air temperature and the decrease in relative humidity , the daily evapotranspiration rate will be higher and will direct effect on irrigation systems, because even occurring a reduction in total evapotranspiration , will require a greater intensity of irrigation to meet the daily demand of crops
Requirements water of cowpea and maize in climate change conditions in the semiarid the brazilian northeast
Keywords: Zea mays L .; Beans - Cowpea; evapotranspiration; Corn - air temperature; Agriculture - climate change; Zea mays L.; Feijão - Caupi; Evapotranspiração; Milho; Agricultura - mudanças climáticas; Temperatura atmosférica; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO